Integration of the Innovation Diffusion Theory (IDT) and the Technology Acceptance Model (TAM) in the Adoption of Learning Management Systems (LMS) - Ali Mujahidin; Day Ramadhani Amir; Boedy Irahdtanto; Ahmad Rizky Wahyu Pratama (Universitas Pendidikan Ganesha, 2025)
The utilization of Learning Management Systems (LMS) in higher education remains suboptimal despite rapid advancements in educational technology. Challenges arise from technical factors and users’ perceptions regarding the system’s usefulness and ease of use. This study aims to analyze and evaluate the factors influencing LMS adoption by integrating Innovation Diffusion Theory (IDT) and Technology Acceptance Model (TAM) to provide a comprehensive understanding of user behavior. A quantitative explanatory approach with a survey method was employed. The study involved 282 respondents, including students and faculty members. The research instrument consisted of questionnaires based on IDT and TAM constructs, while data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 software. The results indicate that out of 12 proposed hypotheses, 10 were supported, and 2 were rejected. Factors such as relative advantage, compatibility, observability, and trialability significantly affected perceived ease of use and perceived usefulness, whereas complexity was not significant. Furthermore, perceived ease of use and perceived usefulness positively influenced behavioral intention to use LMS. These findings confirm that integrating IDT and TAM effectively explains LMS adoption in a holistic manner. Practically, this study provides a foundation for system development, implementation strategies, and higher education policies to enhance LMS utilization, while supporting the adoption of adaptive and sustainable educational technologies.